The Impact of Democratic Parenting in Supporting Children's Personality - Putri, Adinda Eka; Zubaidah, Zubaidah; Rimulawati, Vegestina; Rahmayanty, Dinny; Husna, Nurul (Faculty of Education Universitas Negeri Malang, 2024)
Democratic parenting has been the focus of research in child development psychology over the past few decades. The writing of this article uses a literature study method derived from various articles that are in accordance with the title and problems discussed. This article aims to investigate the impact of democratic parenting on children's personality development. The results of this article show that democratic parenting that involves children in decision-making, provides emotional support, and instills democratic values has a positive impact on children's personality development. Children who come from families with democratic parenting tend to show higher levels of trust, good communication skills, and positive social attitudes. In addition, they also tend to have the ability to manage conflict in a healthier way. These findings prove that democratic parenting can positively shape children's personalities and potentially help them become more independent individuals who contribute positively to society.